2003
DOI: 10.1017/s0033291703008353
|View full text |Cite
|
Sign up to set email alerts
|

Pre-morbid characteristics and co-morbidity of methamphetamine users with and without psychosis

Abstract: Earlier and larger use of MAMP was associated with increased risk of psychosis. Our data are also compatible with the view that pre-morbid schizoid/schizotypal personality predisposes MAMP users to develop psychosis, and that the greater the personality vulnerability, the longer the psychosis will persist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
226
4
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(250 citation statements)
references
References 25 publications
19
226
4
1
Order By: Relevance
“…These findings reinforce the DSM 5 substance-induced psychosis criteria of hallucinations and delusions (American Psychiatric Association, 2013), and they are consistent with past research in showing that delusions in methamphetamine psychosis are primarily persecutory in nature (Akiyama, 2006;Chen et al, 2003;Dore and Sweeting, 2006;Harris and Batki, 2000;Iwanami et al, 1994;Srisurapanont et al, 2003). The affective accompaniment to this psychosis (dominated by depression, suicidality, hostility and self-neglect) is not recognized in the diagnostic criteria for substance-induced psychosis (American Psychiatric Association, 2013) but our results are consistent with Srisurapanont et al (2011), who also found an affective symptom dimension, and other research showing elevated levels of depression among people diagnosed with methamphetamine psychosis relative to other users of the drug (Chen et al, 2003;Lecomte et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings reinforce the DSM 5 substance-induced psychosis criteria of hallucinations and delusions (American Psychiatric Association, 2013), and they are consistent with past research in showing that delusions in methamphetamine psychosis are primarily persecutory in nature (Akiyama, 2006;Chen et al, 2003;Dore and Sweeting, 2006;Harris and Batki, 2000;Iwanami et al, 1994;Srisurapanont et al, 2003). The affective accompaniment to this psychosis (dominated by depression, suicidality, hostility and self-neglect) is not recognized in the diagnostic criteria for substance-induced psychosis (American Psychiatric Association, 2013) but our results are consistent with Srisurapanont et al (2011), who also found an affective symptom dimension, and other research showing elevated levels of depression among people diagnosed with methamphetamine psychosis relative to other users of the drug (Chen et al, 2003;Lecomte et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The affective accompaniment to this psychosis (dominated by depression, suicidality, hostility and self-neglect) is not recognized in the diagnostic criteria for substance-induced psychosis (American Psychiatric Association, 2013) but our results are consistent with Srisurapanont et al (2011), who also found an affective symptom dimension, and other research showing elevated levels of depression among people diagnosed with methamphetamine psychosis relative to other users of the drug (Chen et al, 2003;Lecomte et al, 2013). These collective findings suggest that affective symptoms may be a core feature of the methamphetamine psychosis, perhaps similar to depression with psychotic features or schizoaffective disorder (Tsuang et al, 1982).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The original purpose of CKC's study was to investigate the predisposing factors to methamphetamineinduced psychosis and the results demonstrate that subjects with methamphetamine-induced psychosis may be classified as a distinct group from methamphetamine users. 39 Details of the sampling method and exclusion criteria are mentioned in their work. As the size of the methamphetamine-induced psychosis sample is rather small at this status and may have a different genetic background, here we only examined methamphetamine users without psychosis and the controls.…”
Section: Subjectsmentioning
confidence: 99%
“…Drug users in Taiwan typically have high morbidity of physical and mental illnesses, 15,16 but have little access to mental health services. 16,17 For example, of 325 methamphetamine abusers at a detention center in Taipei, only 8.9% had seen a mental health professional and only 3.1% had been admitted to a psychiatric facility, despite 36.6% reporting that they experienced mental disturbances and 24.3% reporting that they experienced occupational impairment. 16 The majority of these drug abusers did not reveal their use to professionals.…”
Section: Introductionmentioning
confidence: 99%